Motorcycle image application on MATLAB Simulink and FPGA platform - Mat Nong, Mohd Ali; Md Yusof, Juraina; Sabil, Suzila; Mohd Sidek, Roslina; Hasan, Intan Helina; Osman, Rosiah (IEEE, 2019)
This research investigated image tracking and edge detection for motorcycle in various lighting and weather conditions. The capabilities in different resolutions and thresholds level also evaluated. Comparison between hardware and software implementation of edge detection also been made. Developed framework showed great accuracy in segmentation of plate number from motorcycle image in daylight condition compared to rainy daylight and night condition.